Problematika Pendidikan Islam Sebagai Sub Sistem Pendidikan Nasional di Era Global - Choiri, Moch. Miftachul; Fitriani, Aries (AL-TAHRIR, 2011)
A globalization, which looks like both sides of one coin, has both positive and negative impacts. The globalization inspired not only by capitalism but also by pragmatism has practically affected the education in Indonesia. The roles of education become practically unfamiliar and faraway from society needs. The globalization takes some issues such as competence, standardization, and commerce. To face this era, what should Islamic education do as sub-system of national education? The Islamic school (madrasah) as a sub-system of Islamic education in Indonesia, had extremely strong experienced to face the challenges at the last era of Dutch colonialism. The fact that madrasah had not only an autonomy but also an intellectual resources had proven that it could fulfill the needs of Islamic community. These are cultural potencies which should be kept and not be abandoned for the sake of globalization interest. The globalization as a cultural transformation process affects the world, especially the practice of education in Indonesia. All people using science and technology can easily access the global culture. The global culture which is value-free should be faced by transformation of values of which Islamic scholars had transformed in pesantren (Islamic boarding schools) and Islamic schools (madrasah). In other word, both pesantren and madrasah should not be entrapped in capitalism ideology and could serve all people. It is because the paradigm of Islamic education differs from that of both capitalism and pragmatism. The article tries to elaborate how Islamic education in Indonesia especially madrasah should be positioned in the global era